Perfil hepático en el diagnostico de colestasis intrahepática gestacional - Lopez Venegas, Yadira Nataly (2023)
ABSTRACT: Intrahepatic cholestasis is a condition that frequently occurs in pregnant women. Its clinical manifestation usually occurs in the third trimester, and the most common symptom is itching, generally in the hands and feet, which usually disappears after childbirth. The objective of the present investigation was to collect information on the liver profile in the diagnosis of gestational intrahepatic cholestasis. This review was based on a descriptive study with a non-experimental documentary design, cross-sectional and retrospective. The study population was made up of 55 bibliographic references in which inclusion and exclusion criteria were applied, where a sample of 44 publications taken from scientific databases was obtained. Through the analysis and discussion of the results, it was concluded that the liver profile tests: Alanine aminotransferase, Aspartate aminotransferase, Alkaline phosphatase, Gamma-glutamyl transferase, direct bilirubin, indirect bilirubin and bile salts are essential in the analysis of this condition; the tests that provided the greatest contribution to the determination of this disorder are bile acids; cholic acid and chenodeoxycholic acid. The most significant risk factors that influence pregnant women are family history, history of liver pathologies, and multiple pregnancies. Therefore, it is necessary to maintain correct control and performance in patients with this diagnosis; the correct procedure manages to reduce the symptoms and prevents the complications already mentioned. Keywords: Cholestasis, jaundice, pruritus, pregnancy, bile acids.